Iodized Salt and Iodized Water in the Control of Iodine Deficiency Disorders (IDD) in Thailand - Romsai Suwanik (Siriraj Medical Journal, 2020)
The use of drinking water as an additional vehicle for iodine to common salt has its origins in the fact that a low and irregular intake of common salt has led to a high prevalence of goitre in the north of Thailand. The distribution of salt in the north is poor. Culturally water is offered to passers-by and guests in every house. Thus, iodized salt and iodized water are combined to increase the efficacy of both, for children in primary schools in a village in Nan province where goitre is prevalent. At the end of 12 months of a strictly controlled study in 172 placebo and 114 treated subjects, the prevalence in the treated group was reduced dramatically from 60.2 to 10.5%. The urine and serum findings in the post-test samples became normal when compared with those of the pre-test samples. Both iodized salt and iodized water have been used to help relieve iodine deficiency to date. No complications were found in this series of volunteers. Monitoring and evaluation of the method showed that, if the daily dose of iodized salt was consistently 50 ppm and that of iodized water 100 Âµg per litre, this can be continued indefinitely until all areas of the country are fully developed. In conclusion, using combined iodized products under close supervision is definitely more effective than using iodized salt or iodized water alone.